Configuring high-performance work systems in public administration: a set-theoretic approach to explain organizational performance in swiss municipalities - Assanti, Stefano (Frontiers in Political Science, 2025)
High-Performance Work Systems (HPWS) are combinations of human resource (HR) practices designed to enhance organizational performance. Although the configurational approach emphasizes aligning HR practices into coherent bundles (i.e., “best-fit” approach), empirical research has primarily focused on universalistic (i.e., “best-practices”) approaches, especially in the public sector. This study aims to identify which configurations of HPWS practices and work environments better explain the organizational performance of Swiss municipal administrations. Using a set-theoretic approach, the study analyzes data from 119 Swiss municipalities through a revised two-step Qualitative Comparative Analysis (QCA) combined with formal theory evaluation. The results identify a climate of internal trust and a strong HR system as necessary conditions for high performance. Additionally, six distinct HPWS configurations were found to be sufficient for high performance, while three explained low performance. Thus, this study offers empirical support for the configurational perspective in HRM, emphasizing the causal complexity of HPWS and their impact on organizational performance. The findings also reveal that incentive pay and rewards are either consistently avoided or combined with other motivational practices. This underscore significant challenges related to the motivational dimension of the Ability, Motivation, Opportunity (AMO) framework in the public sector, highlighting the need for future research into how motivational HPWS practices can be effectively implemented in alignment with Public Service Motivation (PSM).